Effectiveness of An Educational Program on Elementary Schools’ Teachers' Knowledge about Autism Spectrum Disorders - Asmaa Hammoz Hawas, Wissam Jabbar Qasim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: World Health Organization mentioned that people with autism have a wide range of abilities and requirements, which might change over time. While some persons with autism are able to live independently, others have severe difficulties that necessitate lifelong care and assistance. Autism has a significant influence on schooling and employment prospects. Objective(s): This study aims to determine the effectiveness of an educational program on elementary schools’ teachers' knowledge about autism spectrum disorders. Methodology: A quasi-experimental design (purposive study) used to guide this study, it was applied by the use of pre-post- test approach for two groups of samples (case and control) to determine the effectiveness of an educational program on elementary schools’ teachers' knowledge about autism spectrum disorder in Al-Diwaniyah Educational Directorate during the period from (25th September, 2021) to (1st April, 2022). A non-probability purposive sample was selected from all the schools’ teachers. The total number of teachers who attended to the chosen place during the study period and who fulfilled the study criteria was (50). These (50) teachers were divided into two groups (25) teachers as a group of cases who are exposed to the educational program and (25) teachers who were not exposed to the educational program as a control group. Results of the study: The results exhibit that educational program is highly effective on teachers’ knowledge about autism spectrum disorder in in the study group evidenced by high significant difference in total score of knowledge with regard to post-test at p-value=0.001 respectively. While in the control group, it shows no significant difference in knowledge score. Conclusion: The researcher concludes that the education program was successful in improving the knowledge of the teachers about autism spectrum disorders. This conclusion is illustrated by the statistical methods that display there is an improvement in the study sample knowledge at post-test compared with the pre-test. Recommendations: Educational lectures and workshops should be conducted regularly, updated, and circulated to all teaching staff in elementary schools. Providing elementary schools with an educational booklet prepared by the researcher.